Perception Analysis Of The User Against The Open Green Space In The Campus Area Of Sriwijaya University Indralaya - aries sandratama (Research Centre of Inorganic Materials and Complexs, 2018)
Sriwijaya University campus area, there is the built environment in the form of buildings and good natural environment, in the form of open green spaces are scattered throughout the campus of the Sriwijaya University. Empty land behind the campus planned to be used as open green space that supports the activity of civitas academica campus that includes professors and students. Open green space in the campus, should ideally have a physical function among other things as a function of aesthetic, micro climate controller and shading place and provides the convenience of its users to have activity in the open green space McFarland dkk (2008). Other green open spaces function as supporting educational activities, conservation, recreation and identity. The method used is the survey of the respondents against the respondents using quantitative and qualitative descriptive method. The purpose of the research is to analysis the perception of green open space for student and lecturer at Faculty of Agriculture of Sriwijaya University Indralaya. The numbers of respondents are 151 people. Detailed questionnaire is divided into two characteristics, there are economic and social space requirements. The results of the socio-economic characteristics of the questionnaire are 29.14% of lecturer and student is 70.86%. Questionnaire characteristics space requirements indicate that there are similarities in the educational activities come within the open green space at both the lecturer (50.00%) and students (47.66%) which is practical.